A process evaluation of an on-line fall prevention and management program for individuals who use wheelchairs or scooters living with multiple sclerosis - Van Denend, Toni; Peterson, Elizabeth W.; McArthur, Amy Roder; Yarnot, Rebecca; Kish, Jacqueline; Steinkellner, Sydney; Sandhu, Arman; Rice, Laura A. (Frontiers in Public Health, 2022)
Background: Falls and resulting injury are a significant concern for individuals living with multiple sclerosis that use a wheelchair and/or scooter to support mobility. Effective fall prevention efforts are vital to support the health, well-being, and participation for these individuals. Aims: This study reports the findings from the process evaluation conducted in association with a pilot study evaluating the efficacy of iROLL-O, an on-line, group fall prevention and management program specifically designed for community-based people living with multiple sclerosis who are full-time wheelchair or scooter users. Methods: See below Conclusion: Feedback from key stakeholders was essential to a meaningful process evaluation. Online delivery supported program implementation, including reach, and resulted in high levels of satisfaction among participants and trainers. Future iterations should aim to uphold the positive group context, recruit and train skilled interventionists who are licensed as occupational or physical therapists and continue to provide the program’s diverse approach to fall prevention and management.